Demographic diversity and firm value: A review on large companies using panel data approach - Hassan, R. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper examines the demographic diversity at top-level management and its impact on firm performance. The paper focuses on Upper-echelon theory, which explains board characteristics and firm performance. Theoretical framework is specially designed using concepts, measures and models. Relevant hypotheses are developed to test diversity impact with the use of appropriate variables and measures. A total sample of large 60 top listed companies are considered based on their market capitalization. This empirical work uses BODs attributes and financial data, which are gathered over the period 2009 to 2013. This study incorporates econometrics methodology on panel data analysis, which is used rigorously for hypothesis testing. The results indicate that demographic diversity at board level does have a relationship with market value. Â© 2015 IEEE.